HARMONIZING TRADITIONS AND SUSTAINABLE ECOTOURISM DEVELOPMENT ON BUNGIN ISLAND - Dora Betari; Khairil Anwar; Akhmad Saufi; Mahyuni, Mahyuni; Dwi Putra Buana (Bajang Institute, 2025)
Bungin Island, located in Alas District, Sumbawa Regency, NTB, is known as one of the most populous islands in the world with a unique tradition, namely the practice of building coral to expand the land. This tradition, which has been going on for generations, provides challenges in efforts to develop sustainable ecotourism. This research aims to understand the status of sustainable ecotourism development on Bungin Island and formulate a harmonization strategy between preserving local traditions and environmental conservation needs. This research uses a qualitative approach with in-depth interviews, observation and literature study methods. The research results show that although Bungin Island's cultural and ecotourism potential is enormous, there is a conflict between traditional practices that risk damaging marine ecosystems and environmental conservation efforts. The proposed strategy involves empowering local communities, environmental education, and implementing environmentally friendly technologies to maintain a balance between preserving traditions and developing ecotourism. With a holistic approach, it is hoped that Bungin Island ecotourism can become a model for sustainable tourism management in Indonesia's coastal areas